Acidity improvement of refined-bleached used vegetable oils as dielectric liquid using two-level factorial design - Muhammad Syahrani Johal; Sharin Ab Ghani; Imran Sutan Chairul; Mohd Shahril Ahmad Khiar; Mohamad Nazri Mohamad Din (Institute of Advanced Engineering and Science, 2023)
Recent studies have shown that modifying the chemical structure of used vegetable oils (UVOs) as an alternative dielectric liquid for oil-immersed transformers has improved these oils' physical, electrical and chemical properties. However, previous researchers have implemented the one-factor-at-a-time method as their experimental design approach. Therefore, they overlooked the possibility that combining mixing process parameters at optimum ratios will yield a better result. Hence, in this study, the two-level (2k) factorial design is applied to achieve the lowest acidity level of UVOs through chemical refining process namely as refined-bleached used vegetable oils (RBUVOs). The involved process parameters are oil temperature, mixing speed and mixing time. Based on the results of 23 factorial design, it is found that oil temperature has the most significant effect on acidity, with a percentage contribution of 35.76%. The result also shows that the best mixing process parameters of RBUVOs were: oil temperature (60 °C), mixing speed (1,000 rpm) and mixing time (30 min). Note that these mixing process parameters produced better RBUVOs with an acidity value of 0.0221 mg KOH/g. A regression model is also developed to predict the acidity of RBUVOs as a function of oil temperature, mixing speed and mixing time.